The efficiency, accuracy and acceptability of smartphone-delivered data collection in a low-resource setting – A prospective study. (August 2017) - Raza, Awais; Raza, Ibrahim; Drake, Thomas M.; Sadar, Ahmed Bani; Adil, Muhammad; Baluch, Fatima; Qureshi, Ahmad Uzair; Harrison, Ewen M.; ,
Abstract: Smartphones are increasingly used in healthcare, yet little is known about their utility in medical research as a means of data collection in low- and middle-income countries (LMIC). In this letter, we discuss results from our experiences with data collection on smartphones in an LMIC setting. Our experience found smartphones a secure and reliable data collection tool for medical research that can empower researchers in countries to participate in surgical studies.